Pioneering function of Isl1 in epigenetic regulation during second heart field development - Gao, Rui; Justus Liebig University Giessen (My University, 2019)
Coordinated series of large-scale transcriptional changes and chromatin reorganization drive cell type specification and differentiation during embryogenesis. In this process, pioneer transcription factors play key roles in programming the epigenome and facilitating recruitment of additional regulatory factors. Isl1, a LIM-homeodomain transcription factor, marks the second heart field and plays a key role in early cardiac development. However, the early embryonic lethality of Isl1 knockout mouse makes it impossible to study the role of Isl1 at later stages of mouse heart development. The role of Isl1 in epigenetic regulation during second heart field development and the mechanisms behind are still not clear. In this study, using an Isl1 hypomorphic mouse model, we found Isl1 is critical for cardiac development even at the later stages of embryonic development. To search for the downstream targets of Isl1 during cardiogenesis, we performed RNA-Sequencing with an Isl1 knockout mouse model and the Isl1 hypomorphic mouse model, together with a mESC-based directed cardiac differentiation system. In combination with ChIP in mESC-derived cardiac progenitor cells and in mouse embryos followed by high-throughput sequencing, we identified a regulatory gene network in cardiac progenitor cells and their derivatives organizing by Isl1. To investigate the molecular mechanism underlying the role of Isl1 in second heart field development, we firstly revealed that Isl1 interacts with Brg1 and Baf60c in cardiac progenitor cells by co-immunoprecipitation. We further performed ATAC-sequencing in mESC-derived cardiac progenitor cells and in mouse embryos. Analysis of ATAC-sequencing data, combined with genome-wide profiling of Isl1 binding in mESC-derived cardiac progenitor cells and in mouse embryos, we identified that Isl1 acts as a pioneer factor during cardiogenesis. Moreover, we found Isl1 might recruit Brg1 to its target sites and works cooperatively with the Brg1-Baf60c-based SWI/SNF complex to reorganize the chromatin landscape of target genes with critical functions in cardiac development, thus inducing gene expression programs in cardiac progenitors and promoting cardiac cell fate specification.In conclusion, our study highlights a pioneering function of Isl1 in cardiac lineage commitment and provides exciting novel insights into the molecular machinery orchestrating cardiogenesis.

Während der Embryogenese, bestimmen koordinierte Abfolgen weitreichender transkriptioneller Änderungen und die Reorganisation des Chromatins die Zelltyp-Spezifizierung. Pionertranskriptionsfaktoren stellen in diesem Prozess eine entscheidende Rolle, bei der Programmierung des Epigenoms und der Rekrutierung weiterer regulatorischer Faktoren, dar. Der LIM-homeodomain Transkriptionsfaktor Isl1 ist entscheidend für die frühe Entwicklung des Herzens und fungiert als Marker der kardialen Vorläuferzellen des sogenannten second heart field . Allerdings sind, durch die frühe embryonale Letalität von Isl1-Knockout Mäusen, Studien zur Rolle von Isl1 in späteren Phasen der Herzentwicklung unmöglich. Dadurch bleiben die Funktion von Isl1 in der epigenetischen Regulation der second heart field Entwicklung und die zugrundeliegenden Mechanismen weitgehendst ungeklärt. Im Zuge unserer Studie konnten wir, mittels eines Isl1-hypomorphen Mausmodells, Isl1 als kritischen Faktor für die kardiale Entwicklung während der späten embryonalen Entwicklung identifizieren. Mittels high-throughput sequencing und unter Verwendung eines Isl1-Knockout Mausmodells und des Isl1-hypomorphen Mausmodells in Kombination mit einem gerichteten kardialen Differenzierungssystem, konnten wir ein regulatorisches Netzwerk in kardialen Vorläuferzellen identifizieren, deren Derivate durch Isl1 organisiert sind. Mit Hilfe von Analysen des genomweiten Profilings von Isl1-Bindestellen und von ATAC-Sequenzierungsdaten konnten wir Isl1 als entscheidenden Faktor der frühen Kardiogenese identifizieren. Weiterhin konnten wir zeigen, dass Isl1 mit Brg1 und Baf60c interagiert. Isl1 induziert zusammen mit dem Brg1-Baf60c-basiertem SWI/SNF Komplex Genexpressionsprogramme in kardialen Vorläuferzellen und unterstützt die Zell-Spezifizierung durch die Organisation des Genome. Abschließend konnten wir Isl1 als entscheidenden Pionertranskriptionsfaktor in der kardialen Zelldifferenzierung charakterisieren. Diese Erkenntnisse gewähren Einblicke in die molekularen Mechanismen der Kardiogenese und eröffnen somit neue Möglichkeiten für ein besseres Verständnis der kardialen Entwicklung.
Keywords: ddc:570